2014
DOI: 10.1093/mnras/stu1704
|View full text |Cite
|
Sign up to set email alerts
|

Kompaneets model fitting of the Orion–Eridanus superbubble

Abstract: Winds and supernovae from OB associations create large cavities in the interstellar medium referred to as superbubbles. The Orion molecular clouds are the nearest highmass star-forming region and have created a highly elongated, 20 • x 45 • , superbubble. We fit Kompaneets models to the Orion-Eridanus superbubble and find that a model where the Eridanus side of the superbubble is oriented away from the Sun provides a marginal fit. Because this model requires an unusually small scaleheight of 40 pc and has the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 100 publications
2
37
1
Order By: Relevance
“…Even though the definite extent of the IV gas should be established through an absorption line study that include sightlines covering the entire region shown in Fig. 4, here we argue that that the IV gas traces a structure significantly larger than the dimensions of the Orion-Eridanus superbubble described in previous works (Reynolds & Ogden 1979;Heiles et al 1999;Bally 2008;Pon et al 2014a).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Even though the definite extent of the IV gas should be established through an absorption line study that include sightlines covering the entire region shown in Fig. 4, here we argue that that the IV gas traces a structure significantly larger than the dimensions of the Orion-Eridanus superbubble described in previous works (Reynolds & Ogden 1979;Heiles et al 1999;Bally 2008;Pon et al 2014a).…”
Section: Discussioncontrasting
confidence: 51%
“…Nonetheless, it is possible that individual small-scale structures may still be too bright given their size and distance from Orion OB1 (Pon et al 2014b). Note that some of these filaments lie outside of what has previously been thought to be the edges of the Orion-Eridanus superbubble (Reynolds & Ogden 1979;Heiles et al 1999;Bally 2008;Pon et al 2014a). The dust temperatures measured inside the superbubble aperture and Barnard's Loop are similar to that observed for the entire diffuse sky by Planck (see discussion in Sec.…”
Section: Global Observational Characteristicsmentioning
confidence: 95%
See 2 more Smart Citations
“…In semi-analytical calculations, the thin-shell approximation can be the key to obtaining the expansion of the super-bubble; for example, [5] [6] [7] [8] [9]. The Kompaneyets approximation, see [10] [11], has been used in order to model the super-bubble W4 [9] and the Orion-Eridanus super-bubble [12] [13]. The hydro-dynamical approximation, with the inclusion of interstellar density gradients, can produce a blowout into the galactic halo, see [14] [15].…”
Section: Introductionmentioning
confidence: 99%